MR Imaging Volumetry of Subcortical Structures and Cerebellar Hemispheres in Temporal Lobe Epilepsy - Szabó, C.Á. (AJNR Am J Neuroradiol, 2006)
BACKGROUND AND PURPOSE:There is mounting evidence of extratemporal volume changes associated with medically refractory temporal lobe epilepsy (TLE). This MR imaging study aimed to characterize volume changes in subcortical structures and cerebellar hemispheres with respect to lateralization of the seizure focus, onset and duration of epilepsy, and frequency of generalized tonic-clonic seizures (GTCS). METHODS:Amygdalar, hippocampal, thalamic, caudate head, and cerebellar volume measurements were obtained in the preoperative MR images of 40 patients with TLE (20 right, 20 left), who underwent temporal lobe resection with good outcome, and in 20 right-handed control participants. All 3D MR images were spatially aligned and normalized before measurements were obtained. Standardized volumes and right-to-left volume ratios (VRs) were compared between control participants and right and left TLE groups. Multiple regression analyses were performed to study the effects of epilepsy onset and duration and GTCS frequency on ipsilateral-to-contralateral VRs with respect to the resected seizure focus. RESULTS:Thalamic volumes were smaller bilaterally in patients with TLE. Hippocampal volumes were smaller ipsilateral to the seizure focus, but there was no significant volume loss involving the amygdala, caudate, or cerebellum. Hippocampal and amygdalar right-to-left VRs differed significantly between right and left TLE groups and controls, whereas thalamic right-to-left VRs differed only between the TLE groups. Thalamic ipsilateral-to-contralateral VRs were correlated positively with epilepsy onset and negatively with epilepsy duration. Caudate ipsilateral-to-contralateral VRs were positively, whereas amygdalar and cerebellar VRs were negatively, correlated with GTCS frequency. CONCLUSIONS:Unilateral amygdalar and bilateral thalamic volume loss, in the absence of caudate head atrophy, is likely to reflect seizure-induced injury due to TLE. Correlations of VRs affecting the amygdala, caudate, and cerebellum with GTCS frequency may also reflect injury or a prediposition for secondary generalization. Potential effects of complex partial seizures, febrile seizures, or antiepileptic medications on subcortical structures need to be evaluated in future studies.